A Novel Bioanalytical Method for Simultaneous Determination of Olanzapine and Samidorphan in Human Plasma Using RP-HPLC - Pavani, Bonagiri; Malothu, Narender; Prasanth, DSNBK; Guntupalli, Chakravarthi (Indian Journal of Pharmaceutical Education and Research, 2023)
Background: Schizophrenia patients are given with a combined medication of Olanzapine (OLA) and Samidorphan (SAM). A sensitive bioanalytical RP-HPLC technique has to be needed to analyse these drugs in biological samples, hence we have been developed a method for simultaneous determination of OLA and SAM in human plasma. Materials and Methods: The separation was conducted on a Zorbax SB-C18 column (250 mm x 4.6 mm, 5μ) and an isocratic mobile phase of 10 mM ammonium acetate and acetonitrile (60:40% v/v) at 0.8 mL/min. The quetiapine was employed as Internal Standard (IS). Plasma was treated with phosphoric acid, and then extracted using a HLB cartridge. RP-HPLC coupled with a PDA detector was used for measurement. Results: The SAM, OLA, and IS peaks were appeared at 3.894, 9.572, and 2.318 min, respectively. The method has been found to be sensitive up to 2.25 µg/mL for SAM and 1.00 µg/mL for OLA in human plasma matrix. The method was validated for accuracy, precision, recovery, stability and matrix effect. Solid Phase Extraction (SPE) provided clean samples with good and constant mean recovery:93.32% for SAM, 97.62% for OLA, and 92.78% for IS. The method was linear over 2.25-90 µg/mL and 1-40 µg/mL with R2 ≥0.99 for both analytes, respectively. Three-month stability investigations were carried out at-20°C, 8°C, and room temperature. Conclusion: The developed method was found to be sensitive, accurate, and repeatable, hence it could be applied for routine analysis of these drugs in biological samples.
Keywords: Olanzapine; Samidorphan; Zorbax; Ammonium acetate; Acetonitrile